COMMISSIONS OF INQUIRY AND THE RULES OF EVIDENCE - Warren Freedman (Obiter, 2022)
A commission of inquiry appointed by the president in terms of section 84(2)(f) of the Constitution is entitled, the courts have pointed out on various occasions, to adopt its own procedures, including those related to the receipt of evidence, unless the Commissions Act 8 of 1947 or the president has provided otherwise that is. A commission’s discretion to determine its own procedure is not, however, an unfettered one. This is because, as an organ of state engaged in administrative action, a commission is bound by the provisions of the Promotion of Administrative Justice Act 3 of 2000 and in particular the duty to act fairly. The duty to act fairly does not mean, however, that a commission is bound by the rules of evidence applicable to a court of law. This is because the rules of evidence applicable to a court of law are not determinative of the duty to act fairly. The duty to act fairly is an inherently flexible concept and always depends on the circumstances. A commission is furthermore not a court of law. There are no issues for it to try; there is neither plaintiff nor defendant. Counsel leading evidence for the commission does not perform the functions of a prosecutor and there is no accused. There are no individual parties entitled to a hearing and a verdict on the evidence. Given that it may determine its own procedures, a commission is, the South African courts have pointed out further, responsible for collecting its own evidence. In this respect it may consider information of any nature, including hearsay evidence, newspaper reports, and submissions or representations that are nothing more than opinions. Unfortunately, these principles appear to have been overlooked by the Bloemfontein High Court in Munusamy v Hefer NO (2004 5 BCLR 508 (O)). In this case the court relied, unnecessarily, on the provisions of the Criminal Procedure Act 51 of 1977 to determine whether a summons should be set aside on the grounds that the applicant’s evidence was inadmissible and irrelevant.